2016
DOI: 10.11607/jomi.4061
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Loading of Conical Connection Implants: Up-to-2-Year Retrospective Clinical and Radiologic Study

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 0 publications
0
34
1
Order By: Relevance
“…More importantly, after the initial bone loss, a mean bone gain of 0.11 ± 1.06 mm between the 6-month and 1-year follow-ups was observed, indicating healthy hard-tissue response with this implant. However, the marginal bone remodeling values reported here differ from those of previously published studies evaluating the same implant design [22, 23]. In those studies, the mean marginal bone remodeling at 1 year was −0.42 mm.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…More importantly, after the initial bone loss, a mean bone gain of 0.11 ± 1.06 mm between the 6-month and 1-year follow-ups was observed, indicating healthy hard-tissue response with this implant. However, the marginal bone remodeling values reported here differ from those of previously published studies evaluating the same implant design [22, 23]. In those studies, the mean marginal bone remodeling at 1 year was −0.42 mm.…”
Section: Discussioncontrasting
confidence: 95%
“…This limitation could contribute to the low marginal bone remodeling seen in the previous studies. This conclusion was confirmed by the retrospective study, which showed higher bone loss in healed sites compared with extraction sites [22]. …”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations